Law No. 175/2016 Promulgating the law on: Combating the Information Technology Crimes - egypt (2025)
Part 1 - Part 2 General provisions Procedural provisions and rules - Part-3: Crimes and penalties - Chapter 1: Encroaching on the security of information networks, systems and technologies - Chapter 2: Crimes committed by means of information - Chapter 3: Crimes related to encroaching on privacy and systems and technologies illegitimate informational content - Chapter 4: Crimes committed by the site administrator - Chapter 5: Criminal liability of service providers - Chapter 6: Circumstances dictating the infliction of penal servitude - Chapter 7: Criminal liability of the legal person - Chapter 8: Consequential penalties Chapter – Chapter 9:Attempted commission, and exemption from penalty - Part-4: Transitional and closing provisions